2021
DOI: 10.2176/nmc.oa.2020-0358
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Aneurysms with Internal Carotid Artery Agenesis: A Unique Case Similar to Moyamoya Disease and Literature Review

Abstract: Internal carotid artery (ICA) agenesis/aplasia is occasionally accompanied with cerebral aneurysms caused by hemodynamic stress. If the aneurysms are located around the circle of Willis, they are managed with clipping or coil embolization. Herein, we report a case of ICA agenesis with perforating artery aneurysms treated successfully with revascularization. Moreover, a literature review of ICA agenesis with cerebral aneurysms was performed to compare with the current case. We conducted a literature review usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…ICA agenesis can occur as an isolated vascular defect as seen in our case, but the literature points to a growing association with cerebral aneurysms, with an increased risk of 25-67% [ 16 ]. A study by Zink et al analyzed 165 cases with ICA aplasia or hypoplasia and found that nearly 28% of patients had associated cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…ICA agenesis can occur as an isolated vascular defect as seen in our case, but the literature points to a growing association with cerebral aneurysms, with an increased risk of 25-67% [ 16 ]. A study by Zink et al analyzed 165 cases with ICA aplasia or hypoplasia and found that nearly 28% of patients had associated cerebral aneurysms.…”
Section: Discussionmentioning
confidence: 95%
“…While the exact mechanism linking ICA agenesis with the increased risk of arterial aneurysms is not exactly known, one theory that has been proposed is that the lack of the ICA induces increased Johal et al J Med Cases. 2022;13 (11):536-540 hemodynamic stress due to increased flow through collateral arteries which can, in turn, cause hemorrhage [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 ) Therefore, it is important to screen for intracranial aneurysms in patients with ICA aplasia or hypoplasia. 3 , 4 )…”
Section: Introductionmentioning
confidence: 99%
“…2) Therefore, it is important to screen for intracranial aneurysms in patients with ICA aplasia or hypoplasia. 3,4) Some abnormalities of the craniocervical arteries are as-sociated with neurocristopathy, a developmental abnormality of neural crest cells that can present with vascular abnormalities and craniofacial malformations. 5,6) The Goldenhar syndrome (GS), caused by abnormalities in the first and second branchial arches, is a type of neurocristopathy.…”
Section: Introductionmentioning
confidence: 99%